Scale-up experiments of SO2 removal and the promoting behavior of NO in moving beds at medium temperatures. Issue 15 (26th February 2021) - Ma, Shuangchen; Bie, Xuan; Gong, Chunqin; Qu, Baozhong; Liu, Daokuan
Abstract : A superior desulfurizer, fine NaHCO3 was selected by scale-up experiments. A deep understanding of the reaction process and mechanism was explored. The effect mechanism of NO on desulfurization using NaHCO3 was proposed by in situ FTIR results. Abstract : The dry flue gas desulfurization (FGD) method was studied, which is a part of the integrated removal of multi-pollutants at medium temperatures. Although dry flue gas treatment is a simple and effective method, it is still a highly empirical-led application technology. A superior desulfurization adsorbent, fine powder of NaHCO3 (hereinafter called fine NaHCO3 ), was selected by scale-up experiments. A deep understanding of the reaction process and mechanism is then explored, which helps the further optimization of dry desulfurization. Based on the multi-factor experiments for NaHCO3, the effect mechanism of NO on desulfurization using NaHCO3 is also proposed. The conversion of SO3 2− → SO4 2− is promoted by the existence of NO. Therefore, a slight decline can be found. According to the influences of the SO2 concentration and the residence time, it is concluded that the diffusion of SO2 into the channel of NaHCO3 is the rate-limiting step. Impressively, the reaction process of reactants was clearly studied by in situ FTIR spectroscopy to determine the whole process. Moreover, the recycling of NaHCO3 is the main direction for reducing adsorbent consumption in the next step. The predictable insights are beneficial for profoundly understanding the gas composition synergetic interaction for the SO2 removal by the dry treatment using NaHCO3 .